KAJIAN KEKUATAN ASET DAN KONDISI KERENTANAN PENGHIDUPAN PETANI PADI SEBAGAI DAMPAK ALOKASI RUANG KOTA PADA KORIDOR JALAN HAMPARAN RAWANG - Eki Asmindo; Iwan Rudiarto (Diponegoro University, 2017)
City development plan focuses on enhancing urban functions rather than agricultural activities. This plan usually translated into space allocation of spatial management policy. However, this policy often arises the friction between the functions of urban and agriculture. It circumstance affects the livelihoods of rice farmers. Livelihood assets itself consist of assets of human, financial, social, physical, and natural. Conditions of exposure, sensitivity, and adaptive capacity used in this research to assess the livelihood vulnerability of rice farmers. The quantitative research approach that utilized in this study consists of quantitative descriptive analysis supported by the application of the scoring method to determine the strength conditions of livelihood assets and livelihood vulnerability. Data collection captured by observation, interviews, and questionnaires. Results of this study are of moderate strength to the livelihood assets of the farmers, and their livelihood is quite vulnerable.